2016
DOI: 10.1109/access.2016.2544381
|View full text |Cite
|
Sign up to set email alerts
|

Improving Interdisciplinary Communication With Standardized Cyber Security Terminology: A Literature Review

Abstract: The growing demand for computer security and the cyberization trend are hallmarks of the 21 st century. The rise in cyber-crime, digital currency, e-governance, and more, is well met by a corresponding recent jump in investment in new technology for securing computers around the globe. Recently, business and government sectors have begun to focus efforts on comprehensive cyber security solutions. With this growth has emerged the need for greater methods of collaboration and measurement of security. Despite all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 54 publications
0
19
0
1
Order By: Relevance
“…This relatively new responsibility makes BoDs and executive management teams nervous (Sims, 2019;Abraham et al, 2019). Only a third of IT professionals believe that board members really understand the cyber field (Bay Dynamics, 2015), probably because, despite cyber's ubiquity in modern organizational usage, the core concepts are poorly defined and understood (Ramirez and Choucri, 2016). This lack of clarity gets in the way of organizations achieving their objectives (Althonayan and Andronache, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This relatively new responsibility makes BoDs and executive management teams nervous (Sims, 2019;Abraham et al, 2019). Only a third of IT professionals believe that board members really understand the cyber field (Bay Dynamics, 2015), probably because, despite cyber's ubiquity in modern organizational usage, the core concepts are poorly defined and understood (Ramirez and Choucri, 2016). This lack of clarity gets in the way of organizations achieving their objectives (Althonayan and Andronache, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Terminology is another barrier to integrating cyber risk into an ERM framework on a couple of different levels. Collaboration across academic and industry disciplines is required to manage cyber risk with Ramirez and Choucri (2016), Shameli‐Sendi et al (2016), and Falco et al (2019) arguing that cooperation is hindered by lack of standard cyber risk management terminology. Within enterprises, this often results in the CISO and chief risk officer (CRO) not speaking the same language causing difficulty to integrate cyber risk into ERM risk portfolios (Doherty & Watson, 2017).…”
Section: Future Research: Gaps In Cyber Risk Researchmentioning
confidence: 99%
“…Cyber hygiene detection and security awareness are done in the same way and are done legally [53], [58], [63]. In [27], [55], [57], [59], [60], and [67], the authors suggested that the employees should receive ongoing training in cybersecurity awareness to identify unwanted and suspicious activities in the organization so that users can secure their information.…”
Section: ) Awareness and Training Culturementioning
confidence: 99%
“…The studies [29], [65], [70] reported the amount of awareness a person has regarding cyber-security. Employees should be aware of unauthorized emails [44], [57], [58], [67], text messages, and know that an unauthorized person can access their personal and financial information. [27], [48], [51], [73], [74].…”
Section: ) Awareness Of Riskmentioning
confidence: 99%